Exploring community development as a tool for pro-poor local economic development - Khumalo, Bongokuhle Saselihle (University of the Free State, 2024)
The community of Maluti-a-Phofung faces local economic underdevelopment. Research shows that the apartheid government invested in supporting industrialisation, with 293 operational factories under the municipality that employed close to 30,000 workers (Marais, 2023). However, the new democracy led Maluti-a-Phofung to its downfall economically as most of those industries shut down completely, leaving thousands of poor, unemployed, and marginalised and lacking access to basic services. This collapse was due to poor financial management, corruption allegations, and incompetence that prevented the area from economic progress (Payne, 2017). In Maluti-a-Phofung, approximately 82% of the population still lives on less than $2 per day and being employed does not guarantee that they will be able to move out of poverty. Under-consumption, insufficient investments, and a persistent lack of decent job opportunities undermine the basic social compact, which mandates that all people must contribute to progress and is the cornerstone of democratic countries (ILO, n.d). It is predicted that by 2030, approximately 2 billion young people globally will be unprepared for the workforce if no immediate investment is made in education and skill development (UNICEF Data, 2023). Maluti-a-Phofung is not an exception, as youth unemployment (18- 35) stands at 53% (StatisticSA, 2011). The study explored the effectiveness of community development and pro-poor LED initiatives in reducing poverty, economic underdevelopment, and social inclusion. The study employed a comparative analysis to compare different community development and LED initiatives in South Africa relevant to Maluti-a-Phofung to understand how they operate and achieve their objectives. Sustainable Development Goal (SDG) 8 encourages full and productive employment, equitable, sustainable growth, and decent work for everyone and will also be used as a major to address issues stated in the study (Sorooshian, 2024). Findings revealed that: Community members lack knowledge about LED projects, they do not participate in LED decision-making processes and face unequal access to resource. Furthermore, they struggle with poor service delivery, hindering small business growth and development. The are power dynamics and stakeholder relations that influence and impact LED. However, the municipality involves the community through the Integrated Development Plan. Also, non-profit organisations initiate and advocate for communities to lead LED initiatives. Finally, these organisations facilitate collaboration among stakeholders to manage and implement LED opportunities for community members, Proposals: The proposes actionable recommendations to LED practitioners, policymakers, and funding institutions to conduct workshops and awareness campaigns to educate the community on the opportunities and benefits of LED projects. It also proposes: provision of access to funding, mentorship, and capacity-building programs that will economically empower the community; establishing centres where community members can access information, guidance, and networking opportunities to support entrepreneurship and small businesses, empowering marginalised populations through skill development training, resource access, and education, through crafting poverty reduction strategies and promoting community ownership, social cohesion, and collective action with grass-roots organisations to foster community development and economic empowerment.
Dissertation(MDS (Development Studies))--University of the Free State, 2024
Keywords: Community development; Pro-poor development; Sustainable development; Participatory development; Capacity building; Social capital; Livelihoods; Empowerment; Inclusive development; Bottom-up approach